High Order Thinking Skill in Pre-Service Teachers’ Lesson Plan - Lailatus Sa'adah; Rosi Anjarwati (Universitas Teuku Umar, 2022)
The preparation and implementation of the Lesson Plan is a reflection of the preparation and process of learning activities. The success of the preparation and implementation of lesson plans will greatly affect student learning outcomes. With the change in the curriculum and its approach that leads to High Order Thinking Skills, the preparation and implementation of lesson plans need to be investigated more deeply so that the quality of lesson plans can meet the expectations of learning objectives in particular and national education goals in general. This study intends to find out more clearly about the quality of the preparation and implementation of lesson plans for students who have taken Lesson Plan and Micro Teaching courses. In addition, this study will also analyze the approach used by students in the preparation and implementation of their lesson plans. Using qualitative methods, this research is content analysis because the purpose of this study is to determine the quality of the preparation of student lesson plans. The results indicate that some students’ Lesson Plan has applied HOTS-based with good quality of completeness aspect.